Outside-in Software Development: A Practical Approach to Building Successful Stakeholder-Based Products. (Computer (00189162), 2007)
The article reviews the book "Outside-in Software Development: A Practical Approach to Building Successful Stakeholder-Based Products," by Carl Kessler and John Sweitzer.